ANALISIS KEBIASAAN MEROKOK TERHADAP KEJADIAN TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS PATUMBAK - Novrika Silalahi; Santy Fransiska (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Tuberculosis and smoking is a major problem that have an impact to health problem in the world. Indonesia is one of the country with highest incidence of tuberculosis in the world, and one of the biggest three country that high in smoker consumers. Smoking is not the only one connected with health problem because of uninfected disease, but with higher risk of sickness and death cause of infected diseases, like tuberculosis patients in 2016 is 107 people and smoker with 571 people.Purpose of the reseach is to achieve the connection between smoking habituation with a lot of numbers patients tuberculosis in Health Center Patumbak year of 2017. Usingresearch analitic with case control. Thepopulation in this research come from the patients that seek medication in Health Center Patumbak as much as 89 people. The Purposive of the sampling is used in sampling technique. Gathering the data use interviews with questionnaire. The analysis result showing that majority of smoker 43,8%. The patient with tuberculosis is 80,9%. There’s connection between smoking habituation with tuberculosis.